2011
DOI: 10.5539/ijef.v3n1p262
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Financial Sector Development and Sustainable Economic Development: Time Series Analysis from Pakistan

Abstract: The study empirically investigated the contribution of financial sector in sustainable economic development of Pakistan. Annual data were used from the period of 1973 to 2007. Main objectives were to analyze the long run relationship between financial sector development and sustainable economic development along with direction of causality between both. Auto Regressive Distributed Lag (ARDL) bound testing technique for cointegration was applied to estimate the long run relationship. A stable long run relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…For instance, the feedback hypothesis between financial development and economic growth indicates that financial development boosts economic growth by supplying financial resources to profit oriented investment projects, that is, the supply side, and as a result, financial development is increased because of the rising demand for financial services due to stimulation in the economic growth process, that is, the demand side. This evidence supports the findings of Sofia et al (2010) who reported that financial development leads economic growth in case of Pakistan.…”
Section: Vecm Granger Causality Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, the feedback hypothesis between financial development and economic growth indicates that financial development boosts economic growth by supplying financial resources to profit oriented investment projects, that is, the supply side, and as a result, financial development is increased because of the rising demand for financial services due to stimulation in the economic growth process, that is, the demand side. This evidence supports the findings of Sofia et al (2010) who reported that financial development leads economic growth in case of Pakistan.…”
Section: Vecm Granger Causality Analysissupporting
confidence: 92%
“…demand side. This evidence supports the findings of Sofia et al (2010) who reported that financial development leads economic growth in case of Pakistan.…”
Section: Vecm Granger Causality Analysissupporting
confidence: 82%
“…Sustainable development as a concept captures both short-and longterm dimensions, being viable today and mindful of the future. However, financial development activities and goals are targeted toward immediate needs, which are not always of optimum benefit to the society (Acemoglu & Wolitzky, 2015;Anwar, Shabir & Hussain, 2011). Sustainable development is a focus of activities and deliberate actions to development today, bearing the future in mind.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before examining the dynamic long-and the short-run relationship of human capital and innovation capacity towards economic growth, this study first employs a test for determining the order of integration for each variable. The unit root test is performed using ADF and PP to ensure that there is no variable integrated at I(2) and to avoid misleading estimates or spurious result (Sofia & Ghulam 2011). According to Tursoy and Resatoglu (2017), the unit root test is essential to obtain unbiased test results from empirical studies to determine an equilibrium relationship between variables.…”
Section: Resultsmentioning
confidence: 99%